Territorialização e cultura no cinema documental contemporâneo de Mato Grosso - Araújo, Caroline de Oliveira Santos (2024)
ABSTRACT: It is possible to observe that contemporary documentaries made in Mato Grosso discuss the issue of the globalization of culture concomitant with the decolonial issue. The question formulated to accompany the investigation of this study was: how do contemporary documentary films in Mato Grosso generate forms of visibility and sensitivity for stories and characters that materialize the territory of Mato Grosso? This problematization, moreover, directs the focus of the research, being the driving force of the discussions and also materializes in a second question: how do these films break with the national identification imposed on this territory and promote a new understanding of what Mato would be like? Grosso, its populations and its spaces? What is interesting, then, becomes how the territory is identified in these narratives. The research becomes a cartography of the poetics of contemporary documentary films in Mato Grosso, at the same time as representing, for me as an artist-researcher, a process of self-discovery. With the dilution of geographical, cultural, identity boundaries, among others, due to globalization and internationalization movements, gray zones and contact zones were produced which, from their cores, emerged protagonists who seek to occupy cinematic screens so that their stories have a place and a voice. They are disappeared, immigrants, survivors and unlikely voices who, in their drifts, are what they are, or what they could, or managed to be, in a territory of great natural wealth, with inhospitable pockets and bustling cities and which, in their movements and searches for ideas, purposes and better living conditions, carry with them memories and identities of the territory from which they come. For the discussion, we worked with the notion of globalization of culture, by Renato Ortiz (2007). We also embark on discussions about territory, culture, identity and memory, where we work with authors such as Terry Eagleton, Roque Laraia, Raymond Williams, Homi Bhabha, Arjun Appadurai, Benedict Anderson, Stuart Hall, Anselm L. Strauss, Zygmund Bauman, Ulf Hannerz, Denys Cuche, Giorgio Agamben, Maurice Halbwachs, Pierre Nora, Georg Simmel, among others. In the field of cinema and documentaries, we take as references authors such as Bill Nichols, Guy Gauthier, Hayden White, Cássio Tomaim, Ismail Xavier and Arlindo Machado. The methodology used to observe the films was cartography as thought by Deleuze and studied and applied by Suely Rolnik, Eduardo Passos, Virgínia Kastrup and Liliana da Escóssia.